Hubungan Keperdataan Antara Pengemudi dengan Perusahaan Ojek Online - I Gusti Agung Dhian Maharani Swari Dewi; Ida Ayu Putu Widiati; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2019)
In Indonesia there are interesting phenomena that occur in the community, in the general public consider that drivers of transportation online are one of the employees of the application service company so that between them there is a working relationship, because with the requirements that must be met when registering as a drivers of transportation online. As for the formulation of the problem to be discussed: 1. what is the working relationship between drivers of transportation online and companies as a form of civil relations? 2. What is the legal protection for drivers of transportation online and if the drivers makes interpretations at work? The research aims to find out and understand the relationship between drivers of transportation online and companies as a form of civil relations and legal protection for drivers of transportation online and if the drivers makes interpretations at work. This type of research uses normative legal research or library research methods is the method or method used in legal research carried out by examining existing library materials. In partnership relationships emphasize the principle of mutualism between the two parties, meaning that this relationship as mutually beneficial and where the position of the parties is equal. The principle in legal protection related to government actions rests and comes from the concept of recognition and protection of human right.